Effect of Trading Relationships on Execution Costs in Low-Information-Asymmetry Over-the-Counter Markets - Issa, George; Jarnecic, Elvis (Journal of Financial and Quantitative Analysis, 2019)
Traders can reduce search costs in dealership markets by entering relationships with dealers. However, dealers draw little informational benefit from these relationships in Treasury markets, due to low risk and information asymmetry. We investigate the extent, duration, effects on pricing, and potential benefits of client–dealer relationships. We find that relationship strength leads to higher execution costs for clients, more so during stressed market conditions but less so in the presence of information asymmetry and when trading in corporate bonds. Relationship traders are compensated with immediacy at times when search is costly.